2002
DOI: 10.1084/jem.20020399
|View full text |Cite
|
Sign up to set email alerts
|

Donor-type CD4+CD25+ Regulatory T Cells Suppress Lethal Acute Graft-Versus-Host Disease after Allogeneic Bone Marrow Transplantation

Abstract: Acute graft-versus-host disease (aGVHD) is still a major obstacle in clinical allogeneic bone marrow (BM) transplantation. CD4+CD25+ regulatory T (Treg) cells have recently been shown to suppress proliferative responses of CD4+CD25− T cells to alloantigenic stimulation in vitro and are required for ex vivo tolerization of donor T cells, which results in their reduced potential to induce aGVHD. Here we show that CD4+CD25+ T cells isolated from the spleen or BM of donor C57BL/6 (H-2b) mice that have not been tol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

31
744
2
10

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 1,009 publications
(787 citation statements)
references
References 48 publications
(94 reference statements)
31
744
2
10
Order By: Relevance
“…In this study, upregulation of Treg genes was associated with the absence of GvHD despite donor effector cell administration. 48 All these data including those on the prevention of GvHD 5,6 and our findings highlight the in vivo donor Treg induction/expansion as a promising approach to prevent the deleterious alloreactivity after HC transplantation.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…In this study, upregulation of Treg genes was associated with the absence of GvHD despite donor effector cell administration. 48 All these data including those on the prevention of GvHD 5,6 and our findings highlight the in vivo donor Treg induction/expansion as a promising approach to prevent the deleterious alloreactivity after HC transplantation.…”
Section: Discussionsupporting
confidence: 51%
“…1 Recently, active suppression by CD4 þ CD25 þ regulatory T cells (Treg) has been extensively explored as a mechanism involved in limiting autoimmunity 2,3 as well as a way to induce transplantation tolerance. 4 Thus, CD4 þ CD25 þ Treg cells have been shown to prevent acute graft-versus-host disease (GvHD), 5,6 a frequent complication of allogeneic hematopoietic cell (HC) transplantation. Expression of CD25 is shared by different CD4 þ Treg subsets including CD4 þ CD25 þ 'suppressive' T cells, which act by cell contact-dependent mechanisms, 3,7 IL-10-producing T regulatory type 1 (Tr1) cells 8 and TGF-b-producing Th3 cells.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances have demonstrated that adoptively transferred exogenous Treg can inhibit graft versus host disease (GVHD) [1][2][3]. However, the availability of sufficient numbers of donor Treg for cell-based therapies remains limited [4].…”
Section: Introductionmentioning
confidence: 99%
“…This may be due the fact that some Foxp3 negative cells are also of a regulatory phenotype, such as T regulatory 1 cells [15]. Next, we examined whether these alloantigen-specific iTreg could interfere with the outcome of GVHD as had been described for nTreg [1]. Lethally irradiated (2 Â 4 Gy) BALB/c recipients were transplanted with 5 Â 10 6 Tcell-depleted BM (TCD-BM) plus 5 Â 10 5 MACS-purified Tconv alone, or together with 5 Â 10 5 FACS-sorted nTreg or iTreg.…”
mentioning
confidence: 99%
“…In murine disease models, adoptively transferred Treg prevent, and in some cases, even cure autoimmunity [2,3]. In addition, they protect from graft rejection after allogeneic organ transplantation [4] as well as from graft-versus-host disease after MHCmismatched stem cell transplantation [5][6][7][8]. Recently, a limited number of Phase I clinical trials exploring the adoptive transfer of Treg have been initiated and several additional trials in various clinical settings are in preparation [9,10].…”
mentioning
confidence: 99%